2014
DOI: 10.1590/0103-9016-2013-0191
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort index and infrared temperatures for lambs subjected to different environmental conditions

Abstract: There is an abundance of thermal indices with different input parameters and applicabilities. Infrared thermography is a promising technique for evaluating the response of animals to the environment and differentiating between genetic groups. Thus, the aim of this study was to evaluate superficial body temperatures of lambs from three genetic groups under different environmental conditions, correlating these with thermal comfort indices. Forty lambs (18 males and 22 females) from three genetic groups (Santa In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…Al igual que en este estudio, otras investigaciones plantean el uso de las cámaras termográficas como un método alternativo no invasivo para evaluar el estrés calórico en ovinos (Paim et al, 2014;McManus et al, 2015;Vicente-Pérez et al, 2016;Macías-Cruz et al, 2016) y otras especies (Martello et al, 2010). Las imágenes térmicas captadas por estas cámaras permiten determinar la temperatura de diferentes superficies de pelo, las cuales pueden ser usadas para desarrollar modelos de predicción al estar correlacionadas con TR y FR (McManus et al, 2016), tal como en el presente estudio fue demostrado.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Al igual que en este estudio, otras investigaciones plantean el uso de las cámaras termográficas como un método alternativo no invasivo para evaluar el estrés calórico en ovinos (Paim et al, 2014;McManus et al, 2015;Vicente-Pérez et al, 2016;Macías-Cruz et al, 2016) y otras especies (Martello et al, 2010). Las imágenes térmicas captadas por estas cámaras permiten determinar la temperatura de diferentes superficies de pelo, las cuales pueden ser usadas para desarrollar modelos de predicción al estar correlacionadas con TR y FR (McManus et al, 2016), tal como en el presente estudio fue demostrado.…”
Section: Discussionunclassified
“…Estas imágenes permiten determinar la temperatura de la superficie de diferentes regiones corporales del animal, y relacionar dichas temperaturas con aspectos productivos, reproductivos y de salud animal (Luzi et al, 2013). Al ser la termografía infrarroja un método no invasivo, algunos estudios recomiendan el uso de imágenes termales como indicativo de estrés calórico en ovinos, considerando que hay una asociación positiva entre variables fisiológicas como TR y FR con temperaturas de la capa de pelo o lana obtenidas por termografía infrarroja (Castanheira et al, 2010;George et al, 2014;Paim et al, 2014;Vicente-Pérez et al, 2016).…”
Section: Introductionunclassified
“…Fluctuations in rectal temperature and respiration rate across the observation time were also investigated by Hooper et al (2018) with the lowest value occurred at 6 a.m. morning. Several studies (Paim et al 2014;McManus et al 2015;Seixas et al 2017) reported that the lowest temperatures occurred in the morning and reached its peak at noon.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that long hair can be a heat insulator, serving as a buffer between the environment and the animal’s body [ 30 , 31 ]. An important point to note here is that, in the dry season, although the temperature is high during the day, it can fall well below 10 °C at night [ 32 , 33 ], as skies in this region at this time of year do not have cloud cover, so a lot of heat is lost from the earth’s surface by radiation. While Girolando cows contain Bos taurus taurus genes, and therefore may show a higher resistance to these colder temperatures, Gyr ( Bos taurus indicus) do not have an adaptation to low temperatures [ 34 ].…”
Section: Discussionmentioning
confidence: 99%